Investing in the Livestock Sector : Why Good Numbers Matter, A Sourcebook for Decision Makers on How to Improve Livestock Data - Pica-Ciamarra, Ugo; Baker, Derek; Morgan, Nancy; Zezza, Alberto; Azzarri, Carlo; Ly, Cheikh; Nsiima, Longin; Nouala, Simplice; Okello, Patrick; Sserugga, Joseph (World Bank, Washington, DC, 2014)
This sourcebook summarizes the outputs and lessons of the Livestock in Africa: improving data for better policies project. It aims to present the challenges facing professionals collecting and analyzing livestock data and statistics and possible solutions. While the Sourcebook does not address all conceivable issues related to enhancing livestock data and underlining statistical issues, it does represent a unique document for a number of reasons. To begin with, it is possibly the first document which specifically addresses the broad complexity of livestock data collection, taking into consideration the unique characteristics of the sector. Indeed, in most cases livestock data are dealt with, if ever, within the context of major agricultural initiatives. Second, the sourcebook is a joint product of users and suppliers of livestock data, with its overarching objective being to respond to the information needs of data users, and primarily the Ministries responsible for livestock in African countries and the National Statistical Authorities. Finally, the sourcebook represents a unique experiment of inter-institutional collaboration, which jointly places the World Bank, the FAO Animal Production and Health Division, the ILRI and the Africa Union, Interafrican Bureau for Animal Resources as well as national governments in Niger, Tanzania and Uganda at the forefront of data and statistical innovation for evidence-based livestock sector policies and investments. This sourcebook represents a first step towards a demand-driven and sustainable approach to enhance the livestock information available to decision makers. It is hoped it will provide a useable framework for significantly improving the quantity and quality of livestock data and statistics available to the public and private sector, and also increase the efficacy of investments that country governments and the international community allocate to generate information for livestock sector policies and investments.